The Effect of Health Officer Role to the Program of Stunting Prevention on First 1000 Days of Life in Indonesia (Medico Legal Update, 2020)
A role of health officer to prevent stunting rate was very significant, especially on first 1000 days of life.The role of health officer within program of stunting prevention was divided into three parts: basic role, therole on specific nutritional intervention, since the role on nutritional intervention was regarded as sensitiveaspect. This research aimed to analyze the effect of implementation from health officer to the program ofstunting prevention on the first 1000 days of life, This research was categorized into quantitative researchwhich exerted case control approach, while the data analysis employed bivariate data analysis with logisticregression analysis test. The research sample was taken through cluster random sampling in approximately275 respondents. The result of data analysis showed the effect of health officer basic role to the stuntingprevention. Moreover, the analysis result from those three variables indicated p value ? 0,05, it referred thatthis variable did not get to be confounding factor in this research and it referred that the significant effectwas not existed between health officer role and stunting prevention program on the first 1000 days of lifein Indonesia. This result demonstrated that the variable of specific nutrition intervention became the mosteffective aspect to the program of stunting prevention on the first 1000 day of life, it produced OR value0.703 (95% CI: 0.504-0.981). Therefore, the good specific nutrition intervention has the biggest chance asmuch as 0.703 times in order to prevent stunting rather than the poor specific nutrition intervention.